Pengaruh Penanaman Modal Asing Jepang terhadap Perdagangan Intra-Industri Indonesia-Jepang - Afriandini, Afriandini; Hastiadi, Fithra Faisal (UI Scholars Hub, 2018)
This study analyzes the effect of Japan’s foreign direct investment on Indonesia’s intra-industry trade (IIT) with Japan from 1990-2017. IIT is decomposed into 3 types, horizontal IIT (HIIT), upper vertical IIT (UVIIT), and lower vertical IIT (LVIIT) which indicates quality. The estimation result show that Japanese direct investment have a significant role in enhancing bilateral IIT. Analysis on each type of IIT reveals that Japanese direct investment have positive significant impact on HIIT and LVIIT, but there is no evidence on its impact to UVIIT.